Integration of Stock Markets Between Indonesia and Its Major Trading Partners - Yuliadi, Imamudin; Murpratomo, Sunan Parakitri; Kusumawardani, Dyah Titis (Journal of Economics Research and Social Sciences, 2024)
The aim of this study is to analyse the integration between the emerging stock market of Indonesia and its major trading partners The Research methodology using VECM (Vector Error Correction Model) frameworks, (i.e., US, China, Japan, and Singapore) during the period of January 2016 to December 2018 with monthly data of the Indonesian stock market. The result of is this research found that the Indonesia stock market affected by its major trading partner in short term and long term. Indonesian market (JCI) responds to US market (DJIA) in positive (+) both in short run and long run. Meanwhile, Indonesian market (JCI) responds to Japan market (N225) in negative (-) only in the long run and not significant in the short run. However, China (SCI) and Singapore market (STI) are not significant in short run and long run. This research gap is to explain how the implications of the dynamics of one country's capital market affect the development of stock indexes in other countries. The benefits of this study are to explain the interaction between the dynamics of one capital market in a country and the capital markets of other countries so that appropriate macroeconomic policies can be formulated to anticipate economic effects that have the potential to cause uncertainty in the capital market. The implications of this study provide an overview of the relationship between the development of stock indexes in one country and another.